Relatório de estágio curricular - Ranito, Diana Marlene Pinto da Silva (2020)
The purpose of this work is to describe the incredible experience that I had during four months in the Justices of the Peace Court in Lisbon, in a curricular internship held in the scope of the master's degree in forensic and arbitration at the Faculty of Law of the Universidade Nova de Lisboa under the guidance of Professor João Zenha Martins and Dr. João Chumbinho and Dr. Judite Matias. Firstly, the present work has a theoretical approach to the Peace Courts mentioning its history, and comparing the differences of nowadays, as well as its principles, competence, functioning and process. Adding to this I describe the practical activities that I developed there and the problems that I was confronted with. Along with the report of this experience, the purpose of this work is also to develop a controversial theme that I came along with in the Peace Court. In this case I I will develop the theme "The purchase and sale of a defective thing", thus doing a critical and comparative approach between the general rules of the purchase and sale of defective things that is consecrated on the Civil Code and the rules of Decree-Law no. 67/2003, of April 8, always having as a point of reference a doctrinal and jurisprudential analysis, as usual.